Reflection and transmission of plane acoustic waves in an infinite annular duct with a finite gap on the inner wall - Cinar, Gokhan; Ozturk, Hulya; Cinar, Ozge Yanaz (Wiley-Blackwell, 2011)
The diffraction of acoustic waves by an infinitely long annular duct having a finite gap on the inner wall is investigated rigorously. The related boundary-value problem is formulated into a modified Wiener-Hopf equation, which is then reduced to a pair of simultaneous Fredholm integral equations of the second kind. At the end of the analysis, numerical results illustrating the effects of the width of the coaxial cylindrical waveguide and the gap length on the diffraction phenomenon are presented. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: wave equation; diffraction; scattering; acoustics; annular duct; finite gap; Wiener-Hopf technique